Creative improvisation with a reflexive musical bot. Issue 1 (2nd January 2018) - Brown, Andrew R.
ABSTRACT: This paper discusses improvisatory musical interactions between a musician and a machine. The focus is on duet performances, in which a human pianist and the Controlling Interactive Music (CIM) software system both perform on mechanized pianos. It also discusses improvisatory behaviours, using reflexive strategies in machines, and describes interfaces for musical communication and control between human and machine performers. Results are derived from trials with six expert improvising musicians using CIM. Analysis reveals that creative partnerships are fostered by several factors. The reflexive generative system provides aesthetic cohesion by ensuring that generated material has a direct relationship to that played by the musician. The interaction design relies on musical communication through performance as the primary mechanism for feedback and control. It can be shown that his approach to musical human-machine improvisation allows technical concerns to fall away from the musician's awareness and attention to shift to the musical dialogue within the duet.